Defining Double Capsules: A Clinical and Histological Study. (28th February 2021) - Van Slyke, Aaron C; Roller, Janine M; Alaghehbandan, Reza; Carr, Nicholas J
Abstract: Background: Macrotextured breast implants are associated with double capsules. There is little agreement as to what defines double capsules, how they present, and whether different degrees of double capsule exist. Objectives: This study aimed to define double capsules and report an association between double-capsule type and degree of tissue adherence. Methods: Consecutive aesthetic patients undergoing explantation of Biocell (Allergan, Inc., Irvine, CA) implants between May 2018 and November 2018 were included if they were found to have double capsules intraoperatively. Patient demographics, implant characteristics, explantation reason, implant adherence, and intraoperative findings were recorded. Both adherent and double capsules were histologically examined. Data were analyzed by descriptive statistics. Results: Eleven patients had 22 Biocell implants explanted during the study period. The average explantation time was 8.0 years. Sixteen implants were found to have some degree of nonadherence, and all areas of nonadherence were associated with double-capsule formation. Double capsules were either partial or complete. The architecture of the inner layer of double capsules varied between an organized capsular layer and a thin area of nascent capsule. Histologically, all capsular specimens demonstrated an overall hypocellular fibrous capsule with scattered chronic inflammatory infiltrates. Synovial metaplasia was present in all capsule types and spaces/cracks in the capsule were disproportionately represented in partially adherent capsules. Conclusions: This is the first study to identify a clinical and pathological correlation between double capsules and failed tissue adherence. Double capsules represent a spectrum of inner capsule formation ranging between nascent capsular tissue to a mature inner capsular layer. Level of Evidence: 4: